(untitled) (Portuguese Journal of Family Medicine and General Practice, 2017)
Objective: To determine if there is a relationship between caffeine consumption during preconception and pregnancy and the occurrence of spontaneous abortion or stillbirth in healthy women. Data sources: MEDLINE database, National Guideline Clearinghouse, Canadian Medical Association Practice Guidelines Infobase, Cochrane Library, Bandolier, DARE, Trip Database, and Index of Portuguese medical journals. Methods: An evidence based review of relevant scientific papers published within the past five years (from 01/08/2010 to 31/08/2015), in English, French, Italian, Spanish and Portuguese was conducted. The MESH terms used were ‘caffeine’, ‘spontaneous abortion’ and ‘fetal death’. To evaluate the levels of evidence (LE) and strength of recommendation, the authors used the Strength of recommendation taxonomy of the American Family Physician. Results: The search revealed 84 papers, four of which were included in this survey. We included three systematic reviews (all with LE 2) and one prospective cohort study (LE 1). These papers show an increased occurrence of spontaneous abortion or stillbirth with moderate-to-high consumption of caffeine (over 100-150mg/day) during pregnancy. There is insufficient evidence for an association between these adverse events and caffeine consumption during preconception. Conclusions: Moderate to high caffeine consumption during pregnancy increases the risk of spontaneous abortion and stillbirth (Strength of recommendation B). We recommend that caffeine consumption during this period should be reduced (